Exploring challenges and learning preferences in academic writing among ELT students - Sofiana, Nina; Fitriati, Sri Wuli; Bahri , Seful (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2025)
Academic writing is a critical skill in English Language Teaching (ELT), yet the challenges students face and their learning preferences remain underexplored. While previous studies have examined writing difficulties or learning strategies separately, few have addressed both dimensions in an integrated manner. In response to this gap, the present study investigates the academic writing experiences of ELT students, focusing on their challenges and preferences. Employing a mixed-method design, data were collected from 96 undergraduate students through questionnaires and open-ended responses. The findings reveal that 58.3% had experience writing research proposals, whereas only 49.0% had written theses or journal articles. Key challenges included organizing research data (67.7%), writing the discussion section (71.8%), and connecting results with theoretical frameworks (68.7%). Students also reported low motivation, often relying on deadlines or peer support to complete tasks. In terms of preferences, they emphasized the need for clear instructions, constructive feedback, and level-appropriate materials, while valuing the support of lecturers and peers. These results suggest that academic writing instruction should be structured, differentiated, and project-based, aligned with deep learning principles to enhance engagement, address individual needs, and promote critical thinking and sustainable learning outcomes.